2023
DOI: 10.3389/fendo.2023.1113178
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum carcinoembryonic antigen and cardiometabolic risks: Implication for cardiometabolic prevention

Abstract: BackgroundSerum carcinoembryonic antigen (CEA) is a biomarker commonly used to detect colorectal cancer. CEA levels are affected by many factors, including cardiometabolic diseases, such as cardiovascular diseases (CVDs) and diabetes. Cardiometabolic diseases and cancer share a similar pathological inflammatory pathway, which correlates with an unhealthy lifestyle. Hence, establishing an adequate CEA cut-off value might be a valuable reference for developing precision healthcare programs for cardiometabolic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…8 Moreover, Chang et al has suggested a CEA level of ≥ 3 ng/mL for the early detection and prevention of CMDs through individualized lifestyle modifications. 2 As mentioned earlier, EAT and CEA both have inflammatory characteristics. 2,10 However, reports linking CEA concentration to the EAT do not exist.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…8 Moreover, Chang et al has suggested a CEA level of ≥ 3 ng/mL for the early detection and prevention of CMDs through individualized lifestyle modifications. 2 As mentioned earlier, EAT and CEA both have inflammatory characteristics. 2,10 However, reports linking CEA concentration to the EAT do not exist.…”
mentioning
confidence: 83%
“…2 As mentioned earlier, EAT and CEA both have inflammatory characteristics. 2,10 However, reports linking CEA concentration to the EAT do not exist. Therefore, the present study aimed to investigate the possible association between EAT and CEA.…”
mentioning
confidence: 83%
See 2 more Smart Citations